Investments in Contemporary Russian Artwork as an Alternative Form of Investment - Zamorano-Ford, J (National Research University, Higher School of Econoimics, 2020)
The purpose of this work is to evaluate the efficiency of investments in the artworks of contemporary Russian painters and to compare the effectiveness of these investments with the effectiveness of investments in stock, bond and real estate markets in Russia and the USA. For this research, we first conduct a hedonic regression analysis on the data available for the time period 1950-2019. After that, we build a hedonic price index for the canvases of contemporary Russian artists. A selection of 613 transactions was made, involving canvases from 57 contemporary Russian painters. According to the results of our study, the trend of this index largely reiterates the price behaviour for world contemporary art market. However, the results of this study indicate that investments in contemporary Russian art do not outperform investments in instruments of Russian and American capital and real estate markets. These results were derived by applying the CAPM model, which demonstrated that Russian art as a form of alternative investment is not advisable for the purposes of diversification of investment portfolios. Based on these findings, contemporary Russian art in general can be considered an unattractive instrument for Russian and foreign investors. The scientific novelty of this paper resides in a comparison among those on similar topics. Unlike our study, few of the academic papers published over the last several decades have presented any quantitative analysis with regard to art’s investment performance, and an even smaller amount of research has been devoted to the analysis of Russian art markets. © 2020, National Research University, Higher School of Econoimics. All rights reserved.